The DETERMINATION OF IRON IONS IN RIVER WATERS AND THEIR IMPACT ON THE ECOSYSTEM (Eurasian Journal of Ecology, 2025)
Iron is an important micronutrient in biocenoses. Its balanced presence ensures the normal functioning of ecosystems. However, anthropogenic pollution with iron or artificial addition of iron can disrupt the balance in ecosystems. In this manuscript, we studied the influence of the iron ion in the Oxchu River passing through the Burunlu and Sayifli villages located in Azerbaijan on  various ecosystems. The dynamics of iron ion concentration affecting biosenosis were investigated from January to August. The GPS coordinates of the sampling locations in the river were determined using an Etrex-10 device. Water samples were analyzed in the laboratory using the SM 3030 (A-K) and ISO 11885 methods. The main analyses were performed by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The maximum concentration of iron ions in the Burunlu village section was observed in the first decade of May, reaching 2330 µg/L. In the Oxchu River flowing through Sayifli village, the highest concentration was also observed in the first decade of May. The migration of pollutants in the aquatic environment occurs rapidly; therefore, studying it is extremely important from both ecological and economic perspectives.Key words: clean water, river ecosystem, iron ion, ecology, Inductively Coupled Plasma Optical Emission Spectrometry